Clinical, functional and prognostic correlates of excess left ventricular force in hypertrophic cardiomyopathy. (3rd October 2022) - Palinkas, E D; Marchi, A; Milazzo, A; Tassetti, L; Zampieri, M; D'Alfonso, M G; Mori, F; Palinkas, A; Ciampi, Q; Sepp, R; Olivotto, I; Picano, E
Abstract: Background: Excess force generation during myocardial contraction represents a cardinal feature of hypertrophic cardiomyopathy (HCM). Purpose: To evaluate the anatomical, functional and prognostic correlates of left ventricular (LV) force in HCM. Methods: We prospectively recruited a consecutive sample of 408 HCM patients with LV ejection fraction (EF) >50%, referred for baseline transthoracic echocardiography in 2 primary HCM centers in Hungary and Italy between 1999 and 2021. LV force was calculated as LV outflow tract gradient+systolic blood pressure/LV end-systolic volume. Patients were followed for a median of 107 months (IQ range, 58–158 months), the study endpoint was all-cause mortality. Results: Mean LV force was 6.0±4.6 mm Hg/ml. Receiver-operating characteristic analysis identified 7.5 mm Hg/ml the best cut-off value to predict mortality. LV force >7.5 mm Hg/ml was present in 86 patients (21%), more frequently in women (58 vs 27%, p<0.0001), more often in patients with diabetes (16 vs 6%, p=0.003), beta-blocker (81 vs 58%, p<0.0001), calcium channel-blocker (19 vs 9%, p=0.012) and diuretic therapy (19 vs 8%, p=0.004), compared to patients with LV force ≤7.5 mm Hg/ml. Patients with excess LV force had more advanced NYHA class (1.8±0.7 vs 1.4±0.7, p=0.0001), greater left atrial diameter [(LAd), 46.7±6.6 vs 43.0±7.2 mm, <0.0001], LV maximal wall thickness (23.2±5.5 vs 21.6±5.5 mm p=0.01), LV EF (74.6±6.4 vs 67.0±6.8%, <0.0001), mitral regurgitation grade (1.2±0.7 vs 0.7±0.7, p<0.0001) and E/e' (10.3±5.0 vs 7.8±5.0, p=0.005). During follow-up 43 deaths occurred. All-cause death was more frequent in patients with excess LV force (21 vs 8%, p<0.0001). At multivariable Cox regression analysis, excess LV force was an independent predictor of mortality (HR 2.9, 95% CI 1.14–7.26, p=0.025) independent of age (HR 1.03, 95% CI 1.00–1.05, p=0.022) and LAd (HR 1.07, 95% CI 1.02–1.14, p=0.005). Conclusion: LV force with a threshold of 7.5 mm Hg/ml, independently predicts adverse outcome in patients with HCM and preserved systolic function. Excess LV force generation is associated with female sex, diabetes, NYHA class, medications, LAd, LV wall thickness, EF, mitral regurgitation grade and E/e'. Funding Acknowledgement: Type of funding sources: None.